Impaired synaptic clustering of postsynaptic density proteins and altered signal transmission in hippocampal neurons, and disrupted learning behavior in PDZ1 and PDZ2 ligand binding-deficient PSD-95 knockin mice - Nagura, Hitoshi (BioMed Central, 2012)
BACKGROUND: Postsynaptic density (PSD)-95-like membrane-associated guanylate kinases (PSD-MAGUKs) are scaffold proteins in PSDs that cluster signaling molecules near NMDA receptors. PSD-MAGUKs share a common domain structure, including three PDZ (PDZ1/2/3) domains in their N-terminus. While multiple domains enable the PSD-MAGUKs to bind various ligands, the contribution of each PDZ domain to synaptic organization and function is not fully understood. Here, we focused on the PDZ1/2 domains of PSD-95 that bind NMDA-type receptors, and studied the specific roles of the ligand binding of these domains in the assembly of PSD proteins, synaptic properties of hippocampal neurons, and behavior, using ligand binding-deficient PSD-95 cDNA knockin (KI) mice. RESULTS: The KI mice showed decreased accumulation of mutant PSD-95, PSD-93 and AMPA receptor subunits in the PSD fraction of the hippocampus. In the hippocampal CA1 region of young KI mice, basal synaptic efficacy was reduced and long-term potentiation (LTP) was enhanced with intact long-term depression. In adult KI mice, there was no significant change in the magnitude of LTP in CA1, but robustly enhanced LTP was induced at the medial perforant path-dentate gyrus synapses, suggesting that PSD-95 has an age- and subregion-dependent role. In a battery of behavioral tests, KI mice showed markedly abnormal anxiety-like behavior, impaired spatial reference and working memory, and impaired remote memory and pattern separation in fear conditioning test. CONCLUSIONS: These findings reveal that PSD-95 including its ligand binding of the PDZ1/2 domains controls the synaptic clustering of PSD-MAGUKs and AMPA receptors, which may have an essential role in regulating hippocampal synaptic transmission, plasticity, and hippocampus-dependent behavior.